Preclinical hazard evaluation strategy for nanomedicines. Issue 1 (2nd January 2019) - Siegrist, Stefan; Cörek, Emre; Detampel, Pascal; Sandström, Jenny; Wick, Peter; Huwyler, Jörg
Abstract: The increasing nanomedicine usage has raised concerns about their possible impact on human health. Present evaluation strategies for nanomaterials rely on a case-by-case hazard assessment. They take into account material properties, biological interactions, and toxicological responses. Authorities have also emphasized that exposure route and intended use should be considered in the safety assessment of nanotherapeutics. In contrast to an individual assessment of nanomaterial hazards, we propose in the present work a novel and unique evaluation strategy designed to uncover potential adverse effects of such materials. We specifically focus on spherical engineered nanoparticles used as parenterally administered nanomedicines. Standardized assay protocols from the US Nanotechnology Characterization Laboratory as well as the EU Nanomedicine Characterisation Laboratory can be used for experimental data generation. We focus on both cellular uptake and intracellular persistence as main indicators for nanoparticle hazard potentials. Based on existing regulatory specifications defined by authorities such as the European Medicines Agency and the United States Food and Drug Administration, we provide a robust framework for application-oriented classification paired with intuitive decision making. The Hazard Evaluation Strategy (HES) for injectable nanoparticles is a three-tiered concept covering physicochemical characterization, nanoparticle (bio)interactions, and hazard assessment. It is cost-effective and can assist in the design and optimization of nanoparticles intended for therapeutic use. Furthermore, this concept is designed to be adaptable for alternative exposure and application scenarios. To the knowledge of the authors, the HES is unique in its methodology based on exclusion criteria. It is the first hazard evaluation strategy designed for nanotherapeutics.